Advisory system architecture in agricultural environment to support decision making process. - Mohamed Kassim, Junaidah; Abdullah, Rusli (2012)
The aim of this paper is to proposed software architecture for ontology-driven advisory systems. The architecture reflects the situation in our current agricultural advisory systems where farmers as a client request an advice from the experts to help them in decision making process in their cultivating. The architecture consists of three components, users, module and knowledge/database. Each component complies with the basic process in advisory systems, knowledge acquisition, cognition, and interface. The architecture embeds three approaches in this systems, personalization, knowledge management and ontology. In semantic web architecture all information is spread over the Internet. By using these technologies, we can easily share and reused the information via Internet.